Evaluation of Restricted Antibiotics Utilisation in a Tertiary Care Teaching Hospital - Kumar, Shiv; Kumar, Ashish (Journal of Pharmacy Practice and Community Medicine)
Aim: To assess the prescribing pattern of antibiotics among the inpatients of different wards of hospital, to assess the appropriateness of restricted antibiotics use associated with diagnosis and bacteriological finding, to assess the outcome of restricted antibiotics utilization. Materials and Methods: A prospective observational study was carried out on drug utilization pattern of restricted antibiotics. Case records of patients with restricted antibiotic therapy were reviewed and evaluated using descriptive statistics, mean and standard deviation. A total of 350 filled data entry forms were evaluated and analyzed. Results: Among the total 350 patients selected in which 189 male (54%) and female 161 (54%) were found. Total restricted antibiotics prescribed and administered through various routes are: PO 32 (9.14%), IV 318 (90.85%). Most drugs were given predominantly via IV route in inpatient wards. Different patients conditions like: Fever cases (15.71%) seizure (9.71%), AGE (5.71%), LRTI (1.14%), UTI (0.57%), URTI (1.14%), pneumonia (13.42%), dengue (0.85%), casualty ( 2.28%), dysentery (0.85%), bone fracture (29.42%), surgery(18.57%) etc were treated with restricted antibiotics. Conclusion: The study concludes that, the restricted antibiotics were mostly prescribed as empirical therapy in the study population. These drugs were predominantly administered by IV route for various infections and other pathological conditions. These large numbers of empirical prescriptions of restricted antibiotic shows the need to control of restricted antibiotic use.
Keywords: Multi drug resistance; Antimicrobial; Restricted antibiotics; Alternative therapy; Antimicrobial resistance.